Respostas
respondido por:
2
Boa noite!!! Vamos lá resolver:)
3(2x-3)+x=5
6x -9 + x = 5
6x + x = 5 + 9
7x = 14
x =
x = 2
Espero ter lhe ajudado:) Bons estudos:)
3(2x-3)+x=5
6x -9 + x = 5
6x + x = 5 + 9
7x = 14
x =
x = 2
Espero ter lhe ajudado:) Bons estudos:)
respondido por:
0
Boa tarde
3*(2x - 3) + x = 5
6x - 9 + x = 5
7x = 5 + 9
7x = 14
x = 14/7 = 2
3*(2x - 3) + x = 5
6x - 9 + x = 5
7x = 5 + 9
7x = 14
x = 14/7 = 2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás